Vehicle Lateral Motion Control with Performance and Safety Guarantees. Issue 11 (2016) - Ni, L.; Gupta, A.; Falcone, P.; Johannesson, L.
Abstract: This paper explores the use of Model Predictive Control (MPC) techniques to solve vehicle lateral motion control problem on highway scenarios. In particular, the problem of autonomously driving a vehicle along a desired path is formulated, where safety constraints and performance levels must be guaranteed for all possible road curvatures within a compact set. Safety constraints are translated into a maximum lateral deviation and orientation error w.r.t. a desired path, while performance requirements are formulated in terms of bounded lateral acceleration and velocity. Preliminary simulation results show that the designed controller is capable of delivering acceptable performance at the cost of limited online computational costs.